1995
DOI: 10.1063/1.469329
|View full text |Cite
|
Sign up to set email alerts
|

An abinitio determination of the bending–torsion–torsion spectrum of dimethyl ether, CH3OCH3 and CD3OCD3

Abstract: We have calculated the potential energy hypersurface of dimethyl ether with respect to the COC bending coordinate ␣ and the torsional angles of the two methyl groups, 1 and 2 . Two sets of ab initio calculations were carried out. The first was made at the level MP2/6-31G(d,p) in which the structural coordinates were fully relaxed except for the grid points on the hypersurface. More extensive calculation were carried out with MP4 corrections for electron correlation with the same molecular structure. The torsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 7 publications
2
44
0
Order By: Relevance
“…Barriers of DMA and DMP may be compared with those of dimethylether 29 ͑DME͒ and dimethyl-sulfide 30 ͑DMS͒. The barrier shape and origin of both types of molecules may be correlated.…”
Section: Assignment and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers of DMA and DMP may be compared with those of dimethylether 29 ͑DME͒ and dimethyl-sulfide 30 ͑DMS͒. The barrier shape and origin of both types of molecules may be correlated.…”
Section: Assignment and Discussionmentioning
confidence: 99%
“…23 Fully and partially optimized ab initio calculations can be applied to verify the assignment of IR and Raman spectra. This technique was first employed for a set of molecules showing the G 36 symmetry and two C 3v symmetrical rotors such as thioacetone, 25 acetone, 26 biacetyl, 27 dimethyl-ether, 28,29 dimethyl-sulphide, 30 and butenes. 31 For that purpose, two and three dimension models were used.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral lines come from sources where very well known molecules coexist with uncharacterized species and with already detected ones that are not fully described. In the case of DME, only the vibrational ground state and three fundamental stretching bands of the most abundant isotopologue have been explored, ~ although presumably some of their isotopologues containing either deuterium or 13 C could be identified in the interstellar medium. Many facts concerning their abundances in hot core regions are expected to be clarified with the new observatory ALMA, which was devised as a key instrument for their studies.…”
Section: • Introductionmentioning
confidence: 99%
“…In previous papers, 11,13 we showed that Fermi interactions force us to use a 3D model to obtain accurate band structures. In the present paper, we have applied it for the study of two deuterated species using our previously calculated 3D-PES and our full-dimensional anharmonic force field.…”
Section: • Introductionmentioning
confidence: 99%
“…15 For nonrigid molecules, the theory can help in understanding many aspects related to the effects of barriers on the splitting of the levels. [16][17][18] To take all these effects into consideration, the torsional spectrum of EME is studied, in this paper, from a CCSD͑T͒ three-dimensional potential energy surface ͑3D-PES͒ and a flexible variational model. The 3D-PES determi-nation ͑12 atoms; 181 optimized geometries + zero vibrational energy correction͒ has carried out a large computational effort.…”
Section: Introductionmentioning
confidence: 99%